Modeling of traction electric drive with dc series motors - Шавелкин, Александр Алексеевич; Костенко, Иван Александрович; Герасименко, Виталий Анатолиевич; Мовчан, Анастасия Николаевна (Eastern-European Journal of Enterprise Technologies, 2016)
Analysis of existing models of the Weber-ampere characteristic of the DC motor is performed. It showed that the use of the universal magnetization curve is not always correct, since traction DC motors have local features of design and magnetic system. It is proposed to define the value of the flux КФ as a function of the magnetomotive force of the currents of the series field winding ISFW and the anchor winding IA. The model of the Weber-ampere characteristic of the DC motor is developed. It takes into account the actual values of the currents of the anchor winding and series field winding, which enhances the computation accuracy in the field reduction modes. The structure of the automatic control system of the traction electric drive using the functional converter to determine the field reduction factor based on the above model is proposed.